Unravelling the interrelationships between ecosystem services and human wellbeing in the Bangladesh delta. Issue 2 (4th March 2017) - Hossain, Md Sarwar; Eigenbrod, Felix; Amoako Johnson, Fiifi; Dearing, John A.
ABSTRACT: Coupled social and ecological systems need to be understood from a dynamic perspective in order to operationalise complexity concepts, such as tipping points, for sustainable ecosystem management. In this study, we strive to achieve this type of conceptual understanding through the analysis of the relationships (e.g. strength, nonlinearity) between the trends of ecosystem services (ES) and human wellbeing (HWB) between 1960 and 2010 in the south-west Bangladesh delta using generalized additive and logistic regression models. We use sequential principal components analysis to investigate the connectedness within the social–ecological system as a measure of resilience. We also use published literature to help develop a system dynamic framework in order to investigate how ES and HWB are interlinked. Overall, our results support previous work, which depicts that material wellbeing (basic materials for a good life) having a strong relationship with provisioning services, which in turn, show a weak relationship with the quality of life (security and health). Moreover, our analysis confirms the 'Environmentalist's Paradox' that HWB has increased despite the deterioration in ES. However, our results suggest that provisioning services are not the only important reason for the increases in observed HWB, as these have also been substantially influenced by technology and capital investment (aid and subsidy). In addition, worsening trends in regulation services and in 'slow' variables such as climate suggest that the resilience of the overall social-ecological system is decreasing. Such changes may have severe consequences if they continue, for example, if temperatures exceed the upper physiological limits of key provisioning services (e.g. rice, fish) in the Bangladesh delta. These indicators all suggest that although in terms of HWB the deltaic social–ecological system may be successfully adapting to environmental change, it may also be close to transgressing critical ecological boundaries in the near future.